Late divergence of target and nontarget ERPs in a visual oddball task - Damborská, Alena; Brázdil, Milan; Rektor, Ivan; Koriťáková, Eva; Chládek, Jan; Kukleta, Miloslav (Physiological research, 2012)
Different mental operations were expected in the late phase of intracerebral ERPs obtained in the visual oddball task with mental counting. Therefore we searched for late divergences of target and nontarget ERPs followed by components exceeding the temporal window of the P300 wave. Electrical activity from 152 brain regions of 14 epileptic patients was recorded by means of depth electrodes. Average target and nontarget records from 1800 ms long EEG periods free of epileptic activity were compared. Late divergence preceded by almost identical course of the target and nontarget ERPs was found in 16 brain regions of 6 patients. The mean latency of the divergence point was 570+/-93 ms after the stimulus onset. The target post-divergence section of the ERP differed from the nontarget one by opposite polarity, different latency of the components, or even different number of the components. Generators of post-divergence ERP components were found in the parahippocampal gyrus, superior, middle and inferior temporal gyri, amygdala, and fronto-orbital cortex. Finding of late divergence indicates that functional differences exist even not sooner than during the final phase of the task.
Keywords: Visual Perception; elektroencefalografie; kognitivní evokované potenciály P300; Task Performance and Analysis; lidé středního věku; lidé; ženské pohlaví; duševní procesy; Mental Processes; Time Factors; Reaction Time; Evoked Potentials, Visual; Female; mužské pohlaví; Young Adult; matematické pojmy; epilepsie; Mathematical Concepts; Adult; zraková percepce; Event-Related Potentials, P300; Middle Aged; Brain; Brain Waves; mozek; Epilepsy; plnění a analýza úkolů; Humans; reakční čas; mozkové vlny; zrakové evokované potenciály; dospělí; Male; světelná stimulace; Electroencephalography; mladý dospělý; Photic Stimulation; časové faktory